(untitled) (Fiep Bulletin - online, 2014)
The standard of beauty valued in society associated with thinness ends by emphasizing aspects of form, disregarding the diversity of constitutions that are present in the population and also health aspects. Thus, ideal bodies become objects of desire to be pursued at any cost, having as main target adolescents, who are characterized by instability of an age group still forming. The study is in the final phase of the trial, with the survey data being collected through various instruments. As we have 97 students participating adolescents aged between 14 and 18 years and four physical education teachers from two public schools in Fortaleza. Here we propose to present the methodological procedures which aims to determine the relationship between physical education and school self-concept related to body image of female adolescents.